Election Effect in Malaysian Stock Market: The Case of Trump Effect - Shaha,A.; Elias,S.M.; Karmila Hanim Kamil (Universiti Sains Islam Malaysia, 2024)
The United States Presidential Election in 2016 is marked as one of the historic election in the modern political history as Donald Trump's shocking win raises political risk surrounding the global economy. Amidst the political uncertainties, it is the aim of this study to investigate the presence of this political election effect on the Malaysian stock market. This study observes the existence of abnormal returns of the Kuala Lumpur Composite Index (KLCI) and its 30 constituents, and measures the magnitude of the abnormal returns. This study uses Augmented Dickey-Fuller test to identify the stationary of the data and Ordinary Least Square method to analyze the relationship between the election and the stock returns. The unit root test of the data displays that each variable is stationary at level form. Overall, findings show that the Malaysian stock market is negatively affected by the election as the KLCI slipped by 1% during the Election Day. Six out of thirty constituents of KLCI displays similar negative results with SapuraKencana exhibits the lowest index return. This inferred that the Malaysian stock market is a semi-strong efficient market and is affected by the external general election.